Determining the overstrength factor based on statistical values of European steel grades. Issue 1 (26th May 2020) - Gündel, Max
Abstract: In dissipative seismic design concepts, capacity design rules must be applied to control the plastic mechanism. For this purpose, nondissipative structural elements require an overstrength with respect to dissipative zones. The scattering of the yield strength of structural steel is considered in DIN EN 1998‐1 by the material overstrength factor γ ov with a recommended value of 1.25. However, current measurement data often show significantly higher yield strengths, especially for steel grades of a low nominal strength. In this article, new yield strength data of European steel grades are evaluated and compared with statistical values from the literature. A steel grade‐dependent over strength factor was derived from a new probabilistic model for the yield strength, which has been included in the new German National Annex DIN EN 1998‐1/NA:2018.